Effect of muscle activities on gait for the lower extremities - Nurhanim, K. (Institute of Electrical and Electronics Engineers Inc., 2017)
Gait can be defined as a pattern movement of human limb from one location to another location. Gait can be specified in terms of motor skill functions such as walking, jogging running, and jumping. Walking is the basic form in the human gait study. The aim of this paper is to investigate the effect on muscle activities of human walking on lower extremities in a barefoot condition and wearing of athletic shoe. The experimental work is conducted using the surface electromyography to measure the muscle activities on the lower extremities. It is envisaged that the research would enable improved designs of footwear insole based on the gait analysis to improve pain or injuries of lower extremities. © 2016 IEEE.